A condição da mulher negra na sociedade: por que as mulheres negras vivem em desvantagem? - Souza, Vitoria Carolina da Silva (Universidade Federal do Tocantins, 2024)
This work inquiries about the role of black women in the literary works Quarto de Despejo, by Carolina Maria de Jesus, and Olhos d’água, by Conceição Evaristo, bringing forth the perspectives of theoretical writers such as Lélia González and Regina Dalcastagnè. These authors provide studies about how Black women live in subordinate positions and are consistently treated with inferiority in comparison to white women, exposing the loneliness experienced by them, the abandonment, and the precarious life in the peripheral áreas they live. In this project, our goal is to amplify the voices and celebrate the work of Black authors addressing the topic authentically, revealing the reality of numerous overlooked and marginalized Black women.